Kemampuan Siswa Kelas VIi SMP Negeri 13 Kota Kupang dalam Menulis Teks Cerita Fantasi - Poy, Rejal Rivaldo Martin; Margareta, Karus M; Pekuwali, Dian Sari (Jurnal Lazuardi, 2025)
The focus of this research is "How are the students of Grade VII of SMP Negeri 13 Kupang City able to write fantasy story texts. The purpose of this study is to analyze the ability of grade VII students of SMP Negeri 13 Kupang City in writing fantasy story texts. The theory used is writing theory, because what is measured in this study is the ability of students to write fantasy story texts with the students' own ability to imagine and reason. The method used in this study is qualitative descriptive. In this study, the researcher selected material about fantasy story texts by developing the Independent Kurilkulum found in Class VII in Odd Semester Phase D 7.2.1 Finding information and elements of fantasy texts from visual and audiovisual texts to find explicit and implied meanings. By paying attention to the structure and linguistic aspects of fantasy story texts. A fantasy story text is one of the narrative texts that contains events or events that befall a character that is told in an imaginative nature. The series of events has a flow that starts from orientation, complications, and resolution. Based on the results of the analysis conducted on 27 students of grade VII-A SMP Negeri 13 Kupang City, the ability to write fantasy story texts by paying attention to the structure and linguistic aspects of fantasy story texts can be said to be unsuccessful because, 69% (15 students) were unable to write fantasy story texts with an achievement of 70-100. This is evidenced by the results of the percentage of students who completed or achieved KKM 70 and above amounted to 12 students with a percentage of 44.44% while the students who did not complete amounted to 15 students with a percentage of 55.55%.